Revisiting the “thin months” – a follow-up study on the livelihoods of Mesoamerican coffee farmers - Caswell, M.; Méndez, V.E.; Baca, María; Läderach, Peter R.D.; Liebig, Theresa Ines; Castro Tanzi, S.; Fernández, M. (2014)
Smallholder coffee farmers in Mesoamerica face formidable challenges, including highly variable coffee prices, increasing climate change impacts, and worsening outbreaks of pests and diseases, which contribute to chronic debt and food insecurity. Despite these difficulties, the results of a recent follow-up or longitudinal survey show improvement in key aspects of farmers’ livelihoods, though there is an urgent need to continue working with farmers on these issues. The findings point to promising strategies for enhancing livelihoods, including carefully selected crop diversification practices to improve food security; site-specific instead of blanket recommendations for improved agricultural management and livelihood diversification; access to affordable financing and training in financial literacy; and other education and training programs for farmers.